2010
DOI: 10.1177/0021943610364524
|View full text |Cite
|
Sign up to set email alerts
|

English or a Local Language in Advertising?: The Appreciation of Easy and Difficult English Slogans in the Netherlands

Abstract: Studies have demonstrated frequent use of English in international advertising, but little is known about people's preference for English versus local languages. This article empirically investigated the difficulty of the English language as a possible determinant of people's preference for English or the local language. In an experiment, Dutch participants judged a number of car ads with English slogans that were pretested as easy or difficult to understand. They were subsequently asked to express a preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
71
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 30 publications
7
71
1
Order By: Relevance
“…A similar result was found for non-English examples: Dutch participants found it easier to comprehend French language advertisements where slogans were easy to understand (Hornikx & Starren, 2006). Adaptation of advertisements therefore appears to be the best strategy, but many products are advertised in a range of countries, and then a choice must be made of whether to standardize or adapt (Agrawal, 1995, Jos et al, 2010, with similar considerations to those discussed above.…”
Section: Pharmaceutical Drug Advertising Characteristicssupporting
confidence: 63%
“…A similar result was found for non-English examples: Dutch participants found it easier to comprehend French language advertisements where slogans were easy to understand (Hornikx & Starren, 2006). Adaptation of advertisements therefore appears to be the best strategy, but many products are advertised in a range of countries, and then a choice must be made of whether to standardize or adapt (Agrawal, 1995, Jos et al, 2010, with similar considerations to those discussed above.…”
Section: Pharmaceutical Drug Advertising Characteristicssupporting
confidence: 63%
“…For the difficult French slogans, participants had a preference for ads with the Dutch translations of these slogans (Hornikx and Starren 2006). For the difficult English slogans, there were no differences in preference (Hornikx, van Meurs, and de Boer 2010). The studies by Hornikx and Starren (2006) and Hornikx, van Meurs, and de Boer (2010) used the complexity of slogans (difficult-easy) as a measure of comprehension.…”
mentioning
confidence: 97%
“…For the difficult English slogans, there were no differences in preference (Hornikx, van Meurs, and de Boer 2010). The studies by Hornikx and Starren (2006) and Hornikx, van Meurs, and de Boer (2010) used the complexity of slogans (difficult-easy) as a measure of comprehension. In both studies, the relationship between complexity and comprehension was tested in a pretest, which showed that difficult slogans were more frequently mistranslated and were rated as more difficult than the easy slogans.…”
mentioning
confidence: 97%
See 2 more Smart Citations